STUDI ETNOGRAFI PERILAKU KONSUMTIF FANDOM NCT PADA PEMBELIAN ALBUM DAN MERCHANDISE K-POP - Annisa Rais Marwati; Muhammad Wanadli Rivan; Rawi Diwangkara (Juremi: Jurnal Riset Ekonomi, 2024)
The popular culture that is currently developing widely is Korean culture, which is often called the Korean Wave or Hallyu. The Korean Wave itself has been prepared from the start as a marketing tool to spread the film and music industry or K-Pop. In contrast to the current music industry in other countries which distributes its music digitally, K-Pop music albums are sold physically, not only containing CDs but also adding several components to them as well as selling other merchandise. K-Pop fans feel that buying physical albums is a fan's obligation. This behavior leads to consumer behavior. Physical album sales from the K-Pop music industry have also increased. NCT, one of Korea's popular music groups, recorded popularity with the most album sales which made them win the Album of the Year prize. Consumer consumptive behavior is the study of how individuals or groups carry out the process of purchasing, using and consuming goods, services, ideas or experiences to satisfy their needs and desires. This research uses ethnographic studies to examine fans who actively make large purchases of NCT merchandise worth tens of millions of rupiah. The research results show that fan behavior is dominated by psychological and individual aspects. Fans gain self-satisfaction and social appreciation from socially owned merchandise collections. This is based on self-motivation to gain validation as a true fan